High interindividual variability in habitat selection and functional habitat relationships in European nightjars over a period of habitat change. Issue 12 (7th May 2020) - Mitchell, Lucy J.; Kohler, Tim; White, Piran C. L.; Arnold, Kathryn E.
Abstract: An animal's choice of foraging habitat reflects its response to environmental cues and is likely to vary among individuals in a population. Analyzing the magnitude of individual habitat selection can indicate how resilient populations may be to anthropogenic habitat change, where individually varying, broadly generalist populations have the potential to adjust their behavior. We collected GPS point data from 39 European nightjars ( Caprimulgus europaeus ) at a UK breeding site where restoration measures have altered large areas of habitat between breeding seasons. We calculated individual habitat selection over four breeding seasons to observe changes that might align with change in habitat. We also analyzed change in home range size in line with change in habitat availability, to examine functional relationships that can represent trade‐offs made by the birds related to performance of the habitat. Individual explained more of the variation in population habitat selection than year for most habitat types. Individuals differed in the magnitude of their selection for different habitat types, which created a generalist population composed of both generalist and specialist individuals. Selection also changed over time but only significantly for scrub habitat (60% decrease in selection over 4 years). Across the population, individual home range size was 2% smaller where availability of cleared habitat within the home range was greater, but size increased by 2% where the amount of open water was higher, indicating the presence of trade‐offs related to habitat availability. These results highlight that using individual resource selection and specialization measures, in conjunction with functional responses to change, can lead to better understanding of the needs of a population. Pooling specialist and generalist individuals for analysis could hide divergent responses to change and consequently obscure information that could be important in developing effective conservation strategies. Abstract : Incorporating individual variation into measures of habitat selection can indicate how resilient populations may be to anthropogenic habitat change. We calculated individual‐level habitat selection and individual functional relationships, over four breeding seasons, to observe changes that might align with change in habitat. Individual variation in habitat selection was high, with both specialist and generalist individuals, whose behavior would have been hidden by using a population mean.